Inhaled Phosphodiesterase 4 (PDE4) Inhibitors for Inflammatory Respiratory Diseases - Phillips, Jonathan E. (Frontiers in Pharmacology, 2020)
PDE4 inhibitors can suppress a variety of inflammatory cell functions that contribute to their anti-inflammatory actions in inflammatory respiratory diseases like chronic obstructive pulmonary disease (COPD) and asthma. The systemically delivered PDE4 inhibitor roflumilast has been approved for use in a subset of patients with severe COPD with chronic bronchitis and a history of exacerbations. Use of systemically delivered PDE4 inhibitors has been limited by systemic side effects. Inhaled PDE4 inhibitors have been considered as a viable alternative to increase tolerability and determine the maximum therapeutic potential of PDE4 inhibition in respiratory diseases.